Sondage national des résidents en médecine et directeurs de programme canadiens sur le congé parental durant la résidence - Willoughby, Karen; Julien, Marie; Zendel, Benjamin Rich; Curran, Vernon (Revue canadienne de l’éducation médicale, 2020)
Background: Despite the advantages of having a child as a medical resident, the transition back to residency after parental leave can be challenging. This study is the first to investigate this issue using a nation-wide Canadian sample of both residents and program directors. Method: A questionnaire was developed and made available online. Respondents included 437 female residents, 33 male residents, and 172 residency program directors. The mean length of parental leave was nine months for female residents and six weeks for male residents. Almost all female residents (97.5%) breastfed with an average duration of 12 months. The top challenges reported by residents were feeling guilty for being away from their family, long and unpredictable work hours, sleep deprivation, and finding time to study. When female residents and program directors were matched to both school and program (N = 99 pairs), there was no difference in the total number of challenges reported, but program directors reported offering significantly more accommodations than female residents reported being offered, t(196) = 13.06, p < .001. Results: Our data indicate there is a need for better communication between resident parents and program directors, as well as clear program-specific parental leave policies, particularly for supporting breastfeeding mothers as they return to work.